CONVERSION OF WASTE POLYETHYLENE TEREPHTHALATE (PET) INTO HYDROCARBONS BY PYROLYSIS USING LOCAL MATERIALS AS CATALYSTS - , Ogunbisi, M. A; Ogunyemi, I.O; Okeke, U. A; Ladeji, N. A; Obisanya, A. A; Ajiboye, G.O (IJRDO-Journal of Applied Science, 2020)
Polyethylene terephthalate (PET) have become a general use for various applications such as storage for food and beverages because of its excellent tensile and impact strength, chemical resistance, and thermal stability. However, due to its non-degradability, its waste has continued to generate great concern globally. The recycling of PETs has become a good option for the clean-up of waste PETs in the environment. To this effect, this research aimed at converting waste PETs by pyrolysis into hydrocarbons using local materials as catalyst. Varying ratio of plantain peel and kaolin clay, corn shaft and kaolin and banana peel and kaolin were the local materials used. Agilent 7820A Gas chromatograph attached to a 5977E Mass Spectrometer was used for the analysis. The results indicated that hydrocarbons such as biphenyl, benzonitrile, benzaldehyde, styrene, phenol, benzene, ethylbenzene and naphthalene were among the prominent compounds detected. The results were similar to other research works of PETs pyrolysis using inorganic materials as catalysts hence, the local materials proved to be equally efficient catalysts for PET pyrolysis.